1987
DOI: 10.1111/j.1439-037x.1987.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Leaf Area in Greengram by Non‐destructive Linear Measurements

Abstract: The leaf area by non‐destructive linear measurements have been made in eight cultivars of greengram. The regression equation was Y = 1.58 + 1.79 (X), r = 0.9988** while X = L × W. L and W are the maximum length and width of the terminal leaflet of a trifoliate leaf respectively. Y = leaf area of a trifoliate leaf. This study indicated that this equation can be used for a measuring of the leaf area in situ irrespective of the position of the leaves and variety in greengram. Zusammenfassung Abschätzung der Blatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Variations in leaf shape index and in the LA: LW ratio imply that mungbean leaf area cannot be estimated by some linear function of LW as suggested by Yeboah et al (1983). Manian et al (1987) found no significant difference in the ratios among their varieties that allowed them to generate a unified linear equation for estimating trifoliate leaf area in P. aureus.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Variations in leaf shape index and in the LA: LW ratio imply that mungbean leaf area cannot be estimated by some linear function of LW as suggested by Yeboah et al (1983). Manian et al (1987) found no significant difference in the ratios among their varieties that allowed them to generate a unified linear equation for estimating trifoliate leaf area in P. aureus.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 96%
“…Similar methods were also reported for Vicia faba (Ricciardi et al 1987) and guava (Kobayashi 1988). Manian et al (1987) reported linear measurement of length and maximum width of the terminal leaf in the trifoliate leaves of green gram (Phaseolus aureus). Although they used morphologically different varieties of P. aureus, Manian et al (1987) estimated the whole trifoliate leaf area with a generalized equation for all the eight varieties they studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation